Determinants of skill stability in the workforce among countries - Edgermi Gerasta Gingoyon; Ivy Joy M. Omlang; Angeline Mag-aso Pogoy (Ho Chi Minh City Open University Journal of Science - Social Sciences)
The stability of skills in a workforce is influenced by a range of determinants that can either promote or hinder the ability of employees to maintain and adapt their skills over time. From the 37 country members of the Organization for Economic Cooperation and Development (OECD), the top 15 countries were contrasted in terms of workforce measured by skill stability with the bottom 15 countries using bipolar analysis. This study aimed to determine the predictors of skill stability among the reskilling foci across countries. Data were analyzed using exploratory data, t-tests, and regression analysis. Results revealed that the top 15 countries outperformed the bottom 15 regarding resilience, flexibility, and agility. It was also found that AI and big data, resilience, flexibility, agility, empathy, and active listening were the three predictors of skill stability in the workforce among countries. Hence, it is recommended that organizations and stakeholders explore collaboration opportunities between the top 15 and bottom 15 countries to leverage their respective strengths, ultimately enhancing overall skill stability.